Konseling Eye Movement Desensitization and Reprocessing dalam Mengatasi Post Taumatic Stress Disorder - Evi Winingsih; M. Ramli; Carolina Ligya Radjah (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2021)
Traumatic events are not impossible things in every human life. However, everyone has different coping in dealing with these situations. For some people who experience traumatic events and are unable to cope with the anxiety that arises, they will experience Post Traumatic Stress Desorder (PTSD). The effects of PTSD range from anxiety, insomnia, being unable to forget events, nightmares, and even suicide. This study aims to review counseling that can overcome PTSD problems, namely Eye Movement Desentization and Reprocessing (EMDR). This study uses a recent literature review of several articles on EMDR. Based on the review of the articles conducted, there are several important points, namely (1) the concept of EMDR in the application to overcome PTSD and (2) what are the implications of EMDR for overcoming PTSD. EMDR is one technique that is considered effective in overcoming PTSD problems. Concepts and procedures are discussed.